Differentially expressed miRNAs in anthers may contribute to the fertility of a novel Brassica napus genic male sterile line CN12A - Yun DONG; Yi WANG; Feng-wei JIN; Li-juan XING; Yan FANG; Zheng-ying ZHANG; Jun-jie ZOU; Lei WANG; Miao-yun XU (Journal of Integrative Agriculture, 2020)
In Brassica napus L. (rapeseed), complete genic male sterility (GMS) plays an important role in the utilization of heterosis. Although microRNAs (miRNAs) play essential regulatory roles during bud development, knowledge of how GMS is regulated by miRNAs in rapeseed is rather limited. In this study, we obtained a novel recessive GMS system, CN12AB. The sterile line CN12A has defects in tapetal differentiation and degradation. Illumina sequencing was employed to examine the expression of miRNAs in the buds of CN12A and the fertile line CN12B. We identified 85 known miRNAs and 120 novel miRNAs that were expressed during rapeseed anther development. When comparing the expression levels of miRNAs between CN12A and CN12B, 19 and 18 known miRNAs were found to be differentially expressed in 0.5–1.0 mm buds and in 2.5–3.0 mm buds, respectively. Among these, the expression levels of 14 miRNAs were higher and the levels of 23 miRNAs were lower in CN12A compared with CN12B. The predicted target genes of these differentially expressed miRNAs encode protein kinases, F-box domain-containing proteins, MADS-box family proteins, SBP-box gene family members, HD-ZIP proteins, floral homeotic protein APETALA 2 (AP2), and nuclear factor Y, subunit A. These targets have previously been reported to be involved in pollen development and male sterility, suggesting that miRNAs might act as regulators of GMS in rapeseed anthers. Furthermore, RT-qPCR data suggest that one of the differentially expressed miRNAs, bna-miR159, plays a role in tapetal differentiation by regulating the expression of transcription factor BnMYB101 and participates in tapetal degradation and influences callose degradation by manipulating the expression of BnA6. These findings contribute to our understanding of the roles of miRNAs during anther development and the occurrence of GMS in rapeseed.